Education on the edge of possibility - Caine, Renate Nummela; Caine, Geoffrey (Alexandria, Va. : Association for Supervision and Curriculum Development, 1997)
The authors present their theory of brain-based learning and teaching as a means for school reform, and describe their experiences implementing their ideas in two schools.
Cross currents -- System's end -- Reconceiving the problem -- From machine to the possible human -- How the brain/mind learns -- Teaching for meaning and the expansion of dynamical knowledge -- Introducing our process -- Implementing relaxed alertness -- Implementing immersion and active processing -- Monitoring the learning communities -- Teachers: change and nonchange -- Reality test: Dry Creek and the larger picture -- The edge of possibility.
Includes bibliographical references (p. 259-270) and index.
Adult.
Adult
Keywords: Educational change -- United States -- Case studies; Learning -- Case studies; Teaching -- United States -- Case studies; Education -- Methodology -- Case studies; Learning -- Case studies; Teaching -- Case studies